The Patient Profile of Glaucoma at Ukrida Hospital West Jakarta - Finaria, Adolf; Silaen, Desi Hartati; Lesmana, Michael Indra (Jurnal MedScientiae, 2025)
Glaucoma is the second leading cause of permanent blindness worldwide and often goes undetected until the advanced stages. Risk factors include advanced age, gender, hypertension, diabetes mellitus, and refractive errors such as myopia and hypermetropia. Objective: To describe the demographic and clinical profile of glaucoma patients at UKRIDA Hospital, West Jakarta. Methods: This study used a descriptive cross-sectional design. Data were obtained from the medical records of glaucoma patients examined at UKRIDA Hospital between July 2024 and March 2025. The variables analyzed included age, gender, systemic diseases, refractive errors, and intraocular pressure (IOP). Results: Most patients were over 70 years old (39.7%) and male (61.6%). A total of 49.3% had systemic diseases, primarily hypertension. The most common refractive error was myopia (45.2%). Elevated IOP was found in 26.0% of right eyes and 31.5% of left eyes. Conclusion: Glaucoma patients at UKRIDA Hospital are predominantly elderly males with risk factors such as hypertension and myopia. The presence of normal IOP in many cases suggests the possibility of normal-tension glaucoma. Broader screening and public education are needed for early detection.